TIAP: an observational procedure for assessing family relationships: a clinical case from the parenting evaluation context - Cigala, Ada; Venturelli, Elena; Fruggeri, Laura (Frontiers in Psychology, 2024)
TIAP is an observational procedure to assess family functioning detecting simultaneously the role of each participant and the interdependence of relational behaviors. In particular, the procedure requires family members to play according to different interactive configurations (parent1-children; parent2-children, all together, children and parents as separate units) and therefore different microtransitions from one configuration to another. As such, the procedure allows to study how family members coordinate to maintain stability, promote change, and encourage members to explore different interactive configurations within the family system. TIAP has been validated through several studies conducted with different non-clinical groups of families that have highlighted the salient aspects of family functioning, and significant correlations with variables external to the family system, such as children’s social–emotional competence in the educational context. This paper focuses on the use of TIAP in the contexts of assessing parental competence. Specifically, the article aims to describe, through the reference to a clinical case, the results emerged from a study conducted with 33 families involved in a parenting assessment process. The study is part of a broader collaborative project between the Child and Adolescent Neuropsychiatry Clinic of the Italian National Health Service in Parma, the University of Parma, and the Bologna Family Therapy Center. TIAP was administered to all the families involved as a complement to other tools routinely used for all cases handled by the professionals of the clinic. The coding system includes different indices. Some analyze the interactive family modes: family coordination (mutual attention and responsiveness), the responses to potentials for change (disregard, absorption, amplification), and intra-familiar exploration. Other indices concern the quality of the interactions: the relational triadic dynamic of microtransition (detaching-entrusting-welcoming-joining) and the consistency/inconsistency of the communication channels. The results highlighted how TIAP makes it possible to identify the specific interactive modalities of the different members and their interdependence and reciprocity, favoring the identification of both family weaknesses and family resources, including the children’s contribution. Furthermore, the general data trend showed that TIAP indices detect some important prognostic elements capable of guiding the court’s decisions.